A Product Formula for Volumes of Divisors Via Okounkov Bodies. (8th October 2018) - Choi, Sung Rak; Jung, Seung-Jo; Park, Jinhyung; Won, Joonyeong
Abstract: We generalize Kawamata's product formula for volumes of canonical divisors to arbitrary divisors using Okounkov bodies.